Dual-sense circularly polarized array antenna for GPS L1/L2 bands and L-band satellite receivers - Ahmed Azeez Khudhair; Javad Nourinia; Changiz Ghobadi; Majid Shokri (Scientific Reports)
Abstract A wideband, dual-sense circularly polarized (CP) crossed-dipole array antenna for L-band satellite receivers and GPS L1/L2 bands is presented in this study, addressing conventional designs’ limitations. Using a single wideband double branch-line coupler and planar crossed-dipole arrays, the antenna achieves a measured impedance bandwidth of 57.14% (1.0–1.8 GHz) and an axial ratio bandwidth of 46.72% (1.05–1.69 GHz) as well as axial ratio beamwidths of 66.7°/107.3° for right-hand circular polarization (RHCP) and 82.7°/83.2° for left-hand circular polarization (LHCP), covering both L1 (1.575 GHz) and L2 (1.227 GHz) GPS bands in full. The incorporation of a single wideband double branch-line coupler with dual-band printed dipoles allows for wideband impedance matching and significantly improves the antenna’s performance, achieving a 67% reduction in size compared to the previous design. Furthermore, the proposed configuration in this work simplifies the feeding network and broadens the operational bandwidth of the antenna, making it compatible with a variety of Global Navigation Satellite Systems (GNSSs) and L-band satellite applications. These improvements introduce the proposed antenna as a compact, high-performance, and cost-effective solution for next-generation GNSS/L-band systems.